Presynchronization of estrous cycles in dairy cows before ovsynch + CIDR and resynchronization of repeat estrus using the CIDR - S.Z. El-Zarkouny; J.A. Cartmill; A.M. Richardson; M.A. Medina-Britos (Kansas Agricultural Experiment Station Research Reports, 2001)
Postpartum anestrus is one of the major limitations to achieving acceptable pregnancy rates. The Ovsynch protocol is an excellent tool to improve reproductive efficiency of dairy cows because it can induce estrous cycles in anestrous cows. In the first experiment, administering two PGF2" injections to lactating dairy cows 14 days apart with the second injection given 12 days before the Ovsynch protocol increased (P<0.05) pregnancy rate by 10 percentage points in cycling and noncycling cows. Inserting a progesterone-releasing insert (CIDR) for 7 days during the Ovsynch protocol did not further increase pregnancy rates. In a second experiment, a resynchronization treatment consisting of a used CIDR inserted for 7 days from days 13 to 20 after insemination increased (P<0.05) embryo survival from day 30 to 58 by 11 percentage points but failed to increase overall rate of return to estrus and conception rate at the second AI (first eligible estrus after first AI).; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Ovsynch; Presynch; Pregnancy rates